You matter here: The impact of asset-based pedagogies on learning. Issue 3 (3rd July 2021) - Flint, Amy Seely; Jaggers, Wanda
ABSTRACT: This article describes the impact of asset-based pedagogies in elementary classrooms. Working with concepts such as culturally relevant/sustaining pedagogies, funds of knowledge, and Afro-centric praxis, it is possible to disrupt commonplace and pervasive assumptions about urban and diverse classroom spaces. Drawing from Grade 1 and Grade 4 classrooms, the article highlights a number of engagements that exemplify King and Swartz's culturally informed principles of locating students, multiple ways of knowing and communal responsibility . As a result, teachers and teacher candidates affirm the importance of culturally sustaining and asset-based pedagogies in teacher education and in classrooms to promote well-being, agency and belonging.